TINGKAT STRESS MAHASISWA SELAMA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Wenny Nugrahati Carsita; Bambang Eryanto; Gevpie Adiyuliani (Universitas Prima Indonesia, 2022)
As an effort to prevent and spread Covid-19, the government has implemented online learning activities from home. Online learning causes problems for students due to the availability of internet access, internet quota, the number of assignments given, and a lack of understanding of the material provided. These problems can trigger students to experience stress. The purpose of this study was to determine the stress level of students during online learning during the Covid-19 pandemic. The research method is descriptive. The sample in this study was 171 nursing students using a proportionate stratified random sampling technique. The sampling technique used is proportionate stratified random sampling. The results showed that 52 (30.4%) students experienced mild stress, 115 (67.3%) moderate stress, and 4 (2.3%) severe stress. In this study, it can be concluded that the stress level of students during online learning during the Covid-19 pandemic is moderate level. This research is expected to provide information and descriptions to educational institutions as a follow-up to prevent stress on students.